Respuesta :

Answer:

3x + y = -12.

Step-by-step explanation:

y + 3 = 3(x+5)

y + 3 = 3x + 15

3x + 15 = y + 3

3x - y + 15 = 3

3x + y = -12

Answer:

3x - y = - 12

Step-by-step explanation:

The equation of a line in standard form is

Ax + By = C ( A is a positive integer and B, C are integers )

given

y + 3 = 3(x + 5) ← distribute

y + 3 = 3x + 15 ( subtract y from both sides )

3 = 3x - y + 15 ( subtract 15 from both sides )

- 12 = 3x - y, thus

3x - y = - 12 ← in standard form

ACCESS MORE